2010
DOI: 10.1007/s12032-010-9435-1
|View full text |Cite
|
Sign up to set email alerts
|

Activation of JAK/STAT signal pathway predicts poor prognosis of patients with gliomas

Abstract: JAK/STAT pathway transmits signals from the cell membrane to the nucleus in response to extracellular growth factors and cytokines. Activation of this pathway has been found in certain types of human tumors. The goal of this study was to investigate the correlation between the JAK/STAT pathway in human gliomas and patients' prognosis, which currently is unknown. Western blotting analysis and immunohistochemical staining were performed to detect JAK-1, phosphorylated JAK-1, and STAT-3 expression patterns in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 29 publications
2
46
0
Order By: Relevance
“…As is known, hyper-activation of JAK1-STAT3 signaling pathway has close relationship to the development of certain types of human tumors. Previous studies reported that gliomas patients who possessed high-activation of JAK1 and STAT3 had lower overall survival rates than those with low JAK1 and STAT3 activation (23,27). When the JAK1-STAT3 pathway is activated, STAT3 will be phosphorylated and phosphorylated-STAT3 (p-STAT3) forms dimers and translocates into the nucleus to regulate expression of genes by binding to elements of their promoters.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…As is known, hyper-activation of JAK1-STAT3 signaling pathway has close relationship to the development of certain types of human tumors. Previous studies reported that gliomas patients who possessed high-activation of JAK1 and STAT3 had lower overall survival rates than those with low JAK1 and STAT3 activation (23,27). When the JAK1-STAT3 pathway is activated, STAT3 will be phosphorylated and phosphorylated-STAT3 (p-STAT3) forms dimers and translocates into the nucleus to regulate expression of genes by binding to elements of their promoters.…”
Section: Discussionmentioning
confidence: 93%
“…Activation of this pathway predicts poor prognosis of patients with gliomas (23). Therefore, whether CUEDC2 expression affects the JAK1-STAT3 pathway in transgenic U251 cells was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…An ontological analysis of the microarray data revealed 163 genes to be involved in cell cycle regulation, whose expression was modulated by WWOX overexpression. Among these genes are potent oncogenes linked with brain cancerogenesis: AURKA , KLF8 and JAK1 (1216). In our microarray experiment, the T98G/ WWOX cells demonstrated significantly lower expression of all afore-mentioned genes.…”
Section: Discussionmentioning
confidence: 99%
“…STAT-3 is phosphorylated at two different sites, tyrosine 705 and serine 727 [23]. The tyrosine kinase, JAK-1 phosphorylates STAT-3 at tyrosine 705 [24].…”
Section: Discussionmentioning
confidence: 99%